THE INFLUENCE OF COMPETENCE AND WORK MOTIVATION ON THE PERFORMANCE OF POLSUSPAS MEMBERS AT THE CLASS IIA NARCOTICS PRISON IN JAKARTA - Adi Krisdianto (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to analyze the influence of competence and work motivation on the performance of Polsuspas members at the Class IIA Narcotics Prison in Jakarta. Human resources play a crucial role in achieving organizational goals, particularly in public sector institutions where performance issues are still frequently encountered. Competence and work motivation are considered key factors affecting employee performance. This research employs a quantitative approach using survey methods, with data collected through questionnaires distributed to Polsuspas members. The data were analyzed using multiple linear regression with the help of SPSS, including classical assumption tests and hypothesis testing. The results indicate that competence and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination shows that 96.7% of performance variation can be explained by competence and motivation variables, while the remaining 3.3% is influenced by other factors. Furthermore, work motivation is found to have a more dominant influence compared to competence. In conclusion, improving employee performance requires strengthening both competence and work motivation. Organizations are encouraged to develop integrated human resource management strategies to enhance employee capability and motivation, thereby achieving optimal performance.